The Factors Influencing Tax Management With Company Size As A Control Variable: Factors Influencing Tax Management With Company Size As A Control Variable - Ajitama, Ombih; Pahala, Indra; Ulupui, IGKA (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to obtain empirical evidence on the factors that influence tax management with company size as a control variable. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample of this study was obtained using a purposive sampling method, where only 36 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) could meet all the criteria, so that 108 data were obtained which were used as research samples. The data sources in this study were obtained from secondary data sources, namely, sources or the official website of the Indonesia Stock Exchange www.idx.co.id. The analysis method used is the analysis of the panel data regression model test method. Based on the results of the tests conducted in this study, individually or based on (t-statistic test) it shows that deferred tax burden and profitability individually do not have a significant effect on tax management and capital intensity has a significant effect on tax management, meanwhile company size as a control variable individually does not have a significant effect on tax management.